An Overview of the Performance Improvement Initiatives by the Ministry of Health in the Kingdom of Saudi Arabia - Mazen Hassanain MD, PhD, FRCSC, FACS (SAGE Publishing, 2017)
Saudi Arabia's Ministry of Health (MOH) use corporate performance improvement methodologies to develop and implement performance improvement initiatives designed to continue building on the Ministry's vision of transforming hospital operations and instituting a culture of quality and performance focused on the "patient first" principle. We evaluated the feasibility of setting up a performance improvement unit (PIU) within the MOH to apply the principles of Lean Six Sigma and to change management methodologies. The MOH collaborated with external consultants to implement PIU initiatives in 4 steps: PIU Setup, PIU Capability Building, High-Impact Project Implementation, and Project Sustainability and Knowledge Transfer. PIU units were setup across the 13 provinces over 90 days. The process included the promotion of knowledge sharing to strengthen the skill set of Saudi health care professionals and develop local performance improvement champions within the MOH who could lead, implement, and sustain future projects. Implementation was a challenge; though, early results from the High-Impact Project Implementation phase were encouraging. However, the sustainability of PIU interventions was poor, with performance improvement processes returning to baseline levels within 9 months. This case study shows that PIU implementation is a feasible approach for improving health care delivery in Saudi Arabia. Poor sustainability despite initial success highlights the need to further improve the engagement, incentivization, and training of team leaders and members to achieve long-term success with the program.